Decolonizing knowledge within and beyond the classroom. Issue 1 (2nd January 2021) - Kessi, Shose; Marks, Zoe; Ramugondo, Elelwani
Abstract : This introduction to the second installment of a two-part special issue focuses on actors and spaces that facilitate different forms of progress or push-back in decolonizing African Studies. We map how student activists have served as agents of decolonial change on campuses over time, and argue that intersectional and feminist leadership characterize the current generation of activism. We then explore how classrooms and curricula serve as sites of synthesis between student and faculty activists, and conservative professional and disciplinary norms. Drawing on activist campaigns and articles in the special issue, we present five questions that serve as a starting point for decolonizing courses. Finally, we acknowledge the ways that academic disciplines enforce parochial professional norms and epistemic standards in academia, while also linking academic knowledge production to global marketplaces and intellectual property regimes. We contend that the interplay of these three categories of agents shapes cycles of transformation and patterns of re-consolidation.